2019
DOI: 10.3390/ijms20194899
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Assisted Gene Regulation in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the second-leading cause of cancer death and a major public health problem. Nearly 80% CRC cases are diagnosed after the disease have metastasized and are often too advanced for treatment. Small non-coding RNA guides argonaute protein to their specific target for regulation as the sole of RNA induced silencing complex for gene silencing. These non-coding RNA for example microRNA, are thought to play a key role in affecting the efficiency of gene regulation in cancer, especially CRC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 101 publications
(102 reference statements)
0
14
0
Order By: Relevance
“…Various mechanisms involved in the regulation of CHEK1 expression and activation were previously described [53][54][55]. It can also be regulated at the post-transcriptional level by microRNAs [23,56], which are key regulators of tumor growth and response to treatment [57]. The expression of CHEK1 was further validated, and demonstrated that the CHEK1 gene may possess either oncogenic or anti-oncogenic characteristics, depending on the type of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various mechanisms involved in the regulation of CHEK1 expression and activation were previously described [53][54][55]. It can also be regulated at the post-transcriptional level by microRNAs [23,56], which are key regulators of tumor growth and response to treatment [57]. The expression of CHEK1 was further validated, and demonstrated that the CHEK1 gene may possess either oncogenic or anti-oncogenic characteristics, depending on the type of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The modified method of our previous analysis [56] was employed to investigate the mechanism of action of CHEK1-miR-195 and human argonaute protein in solid tumors. Schrodinger suit, MiRTarBase, Discovery Studio Visualizer (v19.1.0.18287), PROCHECK, PATCHDOCK, RNAfold, and RNA-composer software were all used in this analysis.…”
Section: Molecular Binding Analysismentioning
confidence: 99%
“…The microRNA target genes were used as dataset due to the significance of the associated microRNAs from our previous study (hsa-miR-513b-3p, hsa-miR-500b-3p, hsa-miR-500a-3p, hsa-miR-450b-3p, hsa-miR-193a-5p) along their validated microRNAs hsa-miR-193a-5p, hsa-miR-450b-3p, hsa-miR-501-3p, hsa-miR-501-3p, and hsa-miR-513a-3p). 8 After the assignment of function and the determination of the mechanism of action to these microRNAs and target genes (previous studies), 15,16,23 their genomic profiling deserves closer attention in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, two datasets were queried using the cBioPortal, with the first dataset being the differentially expressed microRNA target genes from our previous in silico studies. 8,15,16 Seven of the genes targeted by our candidate microRNAs that showed significance (Figure 1) were profiled and their expression in CRC was further evaluated. The Colorectal Adenocarcinoma in The Cancer Genome Atlas (TCGA) Colorectal Cancer project (TCGA, Nature 2012) consisting of the whole-exome sequencing in colorectal carcinoma tumor/normal pairs was used as the second dataset.…”
Section: Methodsmentioning
confidence: 98%
“…The molecular docking analysis of AURKA and microRNA of interest was performed by Schrodinger suite, PATCHDOCK, and Discovery Studio Visualizer (DSV) following the approach described by Fadaka et al [90].…”
Section: Protein Preparation Docking and Visualization Analysesmentioning
confidence: 99%